People powered planet hunting with TESS - Eisner, NL (2022)
To date, over 5000 exoplanets have been confirmed, and studies of their characteris- tics have unveiled an extremely wide range of masses, sizes, system architectures, and orbital periods. More than two-thirds of these known planets were identified using dedicated planet detection algorithms that search for transit events in data obtained by space-based survey satellites, such as the Transiting Exoplanet Survey Satellite (TESS). These automated transit detection algorithms are, however, strongly biased towards the detection of short-period planets. For example, 90% of the pipeline- detected TESS planet candidates known to date have orbital periods shorter than 27 days. In this thesis, I show that we can address this period bias by visually inspecting TESS data with the help of a global community of over 30 000 volunteers.